2024
DOI: 10.1083/jcb.202307121
|View full text |Cite
|
Sign up to set email alerts
|

RAS G-domains allosterically contribute to the recognition of lipid headgroups and acyl chains

Neha Arora,
Huanwen Mu,
Hong Liang
et al.

Abstract: Mutant RAS are major contributors to cancer and signal primarily from nanoclusters on the plasma membrane (PM). Their C-terminal membrane anchors are main features of membrane association. However, the same RAS isoform bound to different guanine nucleotides spatially segregate. Different RAS nanoclusters all enrich a phospholipid, phosphatidylserine (PS). These findings suggest more complex membrane interactions. Our electron microscopy-spatial analysis shows that wild-types, G12V mutants, and membrane anchors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Fig.2B shows that gold labeling of GFP-KRAS G12V per 1 μm 2 of PM area in cells expressing LPCAT1 was also significantly lower than that in the V2-expressing cells, suggesting that LPCAT1 expression significantly mislocalizes GFP-KRAS G12V from the PM. Another RAS isoform, HRAS, distributes to spatially separate nanoclusters enriched with different lipids than KRAS 9,10,15,16,19,20 . LPCAT1 expression partially decreased the nanoclustering of GFP-HRAS G12V (Fig.2C), while having no effect on the PM localization of GFP-HRAS G12V (Fig.2D).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fig.2B shows that gold labeling of GFP-KRAS G12V per 1 μm 2 of PM area in cells expressing LPCAT1 was also significantly lower than that in the V2-expressing cells, suggesting that LPCAT1 expression significantly mislocalizes GFP-KRAS G12V from the PM. Another RAS isoform, HRAS, distributes to spatially separate nanoclusters enriched with different lipids than KRAS 9,10,15,16,19,20 . LPCAT1 expression partially decreased the nanoclustering of GFP-HRAS G12V (Fig.2C), while having no effect on the PM localization of GFP-HRAS G12V (Fig.2D).…”
Section: Resultsmentioning
confidence: 99%
“…EGFR dimerization/oligomerization occur in the L o domains or lipid rafts enriched with cholesterol and saturated lipids, which in turn promotes autophosphorylation and signaling 33,42 . On the other hand, KRAS activities occur away from cholesterol in cells 9,10,12,15,1720 . We recently showed that the PM nanoclusters of KRAS oncogenic mutants, such as KRAS G12C , KRAS G12D , KRAS G12V , KRAS G13D and KRAS Q61H , contain PS species with the unsaturated sn-2 chains 20 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations